Formation of longitudinal axon pathways in Caenorhabditis elegans. (January 2019) - Hutter, Harald
Abstract: The small number of neurons and the simple architecture of the Caenorhabditis elegans ( C. elegans ) nervous system enables researchers to study axonal pathfinding at the level of individually identified axons. Axons in C. elegans extend predominantly along one of the two major body axes, the anterior-posterior axis and the dorso-ventral axis. This review will focus on axon navigation along the anterior-posterior axis, leading to the establishment of the longitudinal axon tracts, with a focus on the largest longitudinal axon tract, the ventral nerve cord (VNC). In the VNC, axons grow out in a stereotypic order, with early outgrowing axons (pioneers) playing an important role in guiding later outgrowing (follower) axons. Genetic screens have identified a number of genes specifically affecting the formation of longitudinal axon tracts. These genes include secreted proteins, putative receptors and adhesion molecules, as well as intracellular proteins regulating the cell's response to guidance cues. In contrast to dorso-ventral navigation, no major general guidance cues required for the establishment of longitudinal pathways have been identified so far. The limited penetrance of defects found in many mutants affecting longitudinal navigation suggests that guidance cues act redundantly in this process. The majority of the axon guidance genes identified in C. elegans are evolutionary conserved, i.e. have homologs in other animals, including vertebrates. For a number of these genes, a role in axon guidance has not been described outside C. elegans . Taken together, studies in C. elegans contribute to a fundamental understanding of the molecular basis of axonal navigation that can be extended to other animals, including vertebrates and probably humans as well.